Distribution of extractable heavy metals in different soil fractions - Orroño, Daniela I. (2009)
Due to the difficulties of precisely characterizing environmentally contaminated soil, the effects of heavy metals on plants are studied using uncontaminated soil spiked with known quantities of heavy metals. One problem in using spiked soils is how accurately the distribution of metals mimics stabilized natural soils. We studied the distribution of cadmium, chromium, copper, lead, nickel, and zinc in soil fractions after application in soluble form. The soil samples included a control (an uncontaminated Typic Argiudoll) and two samples spiked with either a moderate or high heavy metal concentration). After application of the salts the soils were subjected to wet/dry cycles over the course of three months. The soils were fractionated using a sequential chemical extraction procedure employing: (1) CaCl2, (2) NaOH, (3) Na2EDTA and (4) HNO3, HCl, and HF. Soil physical separation was carried out by ultrasonic dispersion. The heavy metal levels were determined using ICP-AES. Each heavy metal displayed a unique behavior when added to soil in the form of soluble salts. Cadmium and zinc remained in the soluble fraction, indicating that no equilibrium was attained, while nickel primarily appeared in the insoluble fraction. Chromium, copper and lead were distributed among various soil chemical fractions. The highest levels of all metals appeared in the clay fraction except lead which was mainly present in the silt fraction.